2015
DOI: 10.1371/journal.pone.0138112
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lead Exposure and Mixed Factors of Gender×Age×Brain Regions Interactions on Dendrite Growth, Spine Maturity and NDR Kinase

Abstract: NDR1/2 kinase is essential in dendrite morphology and spine formation, which is regulated by cellular Ca2+. Lead (Pb) is a potent blocker of L-type calcium channel and our recent work showed Pb exposure impairs dendritic spine outgrowth in hippocampal neurons in rats. But the sensitivity of Pb-induced spine maturity with mixed factors (gender×age×brain regions) remains unknown. This study aimed to systematically investigate the effect of Pb exposure on spine maturity in rat brain with three factors (gender×age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…However there is uncertainty on the mechanism by which lead (Pb) gets into the brain. Rahman et al (2012) and Du et al (2015) reported significantly higher level of lead accumulation in the brain of rat pups exposed to Pb postnatally, though this contrasted the work of Lindquist et al (2015) who reported a non-significant accumulation of lead after perinatal exposure to lead. The activity of the hippocampus is distorted particularly in children by exposure to lead.…”
Section: Introductioncontrasting
confidence: 63%
“…However there is uncertainty on the mechanism by which lead (Pb) gets into the brain. Rahman et al (2012) and Du et al (2015) reported significantly higher level of lead accumulation in the brain of rat pups exposed to Pb postnatally, though this contrasted the work of Lindquist et al (2015) who reported a non-significant accumulation of lead after perinatal exposure to lead. The activity of the hippocampus is distorted particularly in children by exposure to lead.…”
Section: Introductioncontrasting
confidence: 63%
“…In fact, our data could reflect the long‐term restoration of presynaptic mechanisms back to normal state, a compensatory effect that can occur even under continuous Pb exposure, given enough time. As published using rats continuously exposed to high‐level Pb from birth to the experimental day 30, 60, or 90 (Du et al, ), pyramidal neurons exhibited some cytoarchitectural changes that were obvious at PND 30, but then absent at PND 60 and PND 90. Since PPR was not affected, changes we observed in basal neurotransmission detected could result from postsynaptic mechanisms (e.g., NMDA receptor expression, activation, and distribution).…”
Section: Discussionmentioning
confidence: 57%
“…This is similar to previous studies using male and female rats exposed to Pb prenatally until PND 21 (BLLs = 16.04–30.1 µg/dl), showing no effect on basal synaptic transmission or population spike amplitude in areas CA1, CA3, and dentate gyrus 30–45 days postexposure (Gutowski, Altmann, Sveinsson, & Wiegand, ; Xu et al, ; Zhao et al, ). Interestingly, the density of dendritic spines decreased in HPC neurons from rats continuously exposed to high‐level Pb from parturition to PND 30, 60, or 90 (BLLs = 21–38 µg/dl; Du et al, ). A decrease in spine density is typically associated with a decrease in synaptic transmission, which we did not observe in the mice exposed to high‐level Pb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects on the peripheral nervous system are more pronounced in adults while the central nervous system is more prominently affected in children As the main target for lead toxicity is the CNS, the brain is the organ most studied in lead toxicity (Winder and Kitchen, 1984). Lead neurotoxicity occurs when the exposure to lead alters the normal activity of the CNS and causes damage to the CNS (Nava-Ruíz and Méndez-Armenta, 2013; Du et al, 2015). The direct neurotoxic actions of lead include apoptosis (programmed cell death), excitotoxicity affecting neurotransmitter storage and release and altering neurotransmitter receptors, mitochondria, second messengers, cerebrovascular endothelial cells, and both astroglia and oligodendroglia (Flora et …”
Section: Neurotoxicitymentioning
confidence: 99%